2021
DOI: 10.3390/ijms222413599
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and Morphine in the Treatment of Chronic Neuropathic Pain–A Biomedical Mechanism of Action

Abstract: The effectiveness of opioids in the treatment of neuropathic pain is limited. It was demonstrated that magnesium ions (Mg2+), physiological antagonists of N-methyl-D-aspartate receptor (NMDAR), increase opioid analgesia in chronic pain. Our study aimed to determine the molecular mechanism of this action. Early data indicate the cross-regulation of µ opioid receptor (MOR) and NMDAR in pain control. Morphine acting on MOR stimulates protein kinase C (PKC), while induction of NMDAR recruits protein kinase A (PKA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The functional state of NMDARs in the central nervous system is mainly regulated by Mg 2+ . As a physiological antagonist of NMDARs, Mg 2+ can block the calcium influx of the channel and maintain the resting membrane potential (Kulik et al, 2021 ). The depolarization process removes the Mg 2+ -induced blockade of NMDARs in a voltage-dependent manner, resulting in hyperexcitability and consequently a sustained state of depolarization and increased synaptic strength (Johnson and Ascher, 1990 ).…”
Section: The Regulation In the Expression And Activation Of Nmdarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional state of NMDARs in the central nervous system is mainly regulated by Mg 2+ . As a physiological antagonist of NMDARs, Mg 2+ can block the calcium influx of the channel and maintain the resting membrane potential (Kulik et al, 2021 ). The depolarization process removes the Mg 2+ -induced blockade of NMDARs in a voltage-dependent manner, resulting in hyperexcitability and consequently a sustained state of depolarization and increased synaptic strength (Johnson and Ascher, 1990 ).…”
Section: The Regulation In the Expression And Activation Of Nmdarsmentioning
confidence: 99%
“…Similarly, Mg 2+ deficient rats develop mechanical hyperalgesia, which is reversed by NMDAR antagonists (Begon et al, 2001 ). Preclinical studies have found that the combination of Mg 2+ and opioids can relieve neuropathic pain in diabetic rats by reducing the level of PKA in the PAG and increasing opioid receptor activity, indicating that Mg 2+ can be used as a supplement for the treatment of pain (Rondon et al, 2010 ; Kulik et al, 2021 ). In addition to Mg 2+ , in vitro studies on mouse hippocampal neurons have confirmed that Zn 2+ can selectively block NMDAR-mediated central neuron excitation (Westbrook and Mayer, 1987 ; Choi and Lipton, 1999 ; Morabito et al, 2022 ).…”
Section: The Regulation In the Expression And Activation Of Nmdarsmentioning
confidence: 99%
“…Under normal resting potential, Mg 2+ ions blocked the pore of NMDAR. However, when the membrane was depolarized, the Mg 2+ left NMDAR and allowed free entry of Ca 2+ , which eventually led to neuronal loss [ 114 ]. Furthermore, a strong correlation between NKA deficiency and oxidative stress was reported in HD.…”
Section: The Role Of Nka In Huntington’s Diseasementioning
confidence: 99%
“…Magnesium, acting as an N-methyl-D-aspartate (NMDA) receptor antagonist, has garnered attention as a potential adjuvant to opioids, theorized to possess analgesic properties due to its modulation of pain transmission pathways within the central nervous system 4,5…”
Section: Introductionmentioning
confidence: 99%